A finite-element method for determining ohmic distortion of current-voltage curves at hydrodynamic electrodes - Coles, B; Compton, R; Spackman, R (1993)
A finite-element method is described that predicts the effects of ohmic distortion of current-voltage curves for arbitrary cell and hydrodynamic electrode geometries using the widely available circuit analysis program SPICE. Simulated and experimental data are presented for a channel electrode flow cell showing the displacement of the half-wave potential and the potential-dependent error in the Tafel slope for the case of an electrochemically reversible electrode reaction. Error curves are provided that may be scaled for different electrolyte conductivities as a guide to the maximum current levels that may be used in practice. For analytical flow detection work, the displacement of the half-wave potential under certain conditions implies that high detection potentials must be used to obtain the correct concentration-related current intensity. The implications for quantitative measurements using practical electrodes are assessed.